Analysis of Customer Satisfaction Using the Service Quality (SERVQUAL) and Importance-Performance Analysis (IPA) Methods at Perumdam, Grobogan Regency - iriani Iriani; M. Ibnu Ma'nail (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Perumdam Purwa Tirta Dharma in Grobogan Regency, as a clean water service provider, is expected to meet customer expectations; however, the high number of complaints received indicates that the quality of service provided is not yet optimal. This study aims to analyze customer satisfaction levels using the Service Quality (SERVQUAL) method and to identify service attributes that should be prioritized for improvement through Importance-Performance Analysis (IPA). The study employed a quantitative approach using a questionnaire distributed to 100 active customers selected via random sampling. The results of the SERVQUAL analysis showed that all five dimensions of service quality had negative gap values, with the Tangibles dimension exhibiting the largest gap (?2.158), followed by Assurance (?2.046), Reliability (?2.026), Empathy (?2.002), and Responsiveness (?1.982), indicating that the overall service received by customers still falls short of their expectations. The IPA mapping results identified five attributes in the top-priority quadrant: clarity of service information, provision of clean water, staff appearance, speed of complaint response, and staff courtesy in serving customers. These findings serve as the basis for the company to focus on improving these five attributes by enhancing staff competence, developing clearer standard operating procedures (SOPs) for handling complaints, and implementing a digital complaint system, thereby increasing customer satisfaction and loyalty. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 9: Industry, Innovation and InfrastructureSDG 11: Sustainable Cities and CommunitiesSDG 16: Peace, Justice and Strong Institutions